Zonificación ecológica del cerro "El Potosí", Galeana, Nuevo León, México - Mario A. García A.; Eduardo Javier Treviño Garza; César M. Cantú Ayala (Investigaciones Geográficas, 1999)
As part of the proposal made in order to declare "El Potosí" mountain as a special biosphere reserve, an ecological zonification map was made considering the nucleus zone, buffer and habitat rehabilitation. Criteria used for zonification the distribution of vegetation and wildlife populations, taken from cartographic interpretation using a satellite image and information of biodiversity. Ten vegetation types and four land-uses were defined, 45 species were found at a special conservation status: 19 of them are plants and 26 are animals.